Factors relating to home telehealth acceptance and usage compliance - Wade R; Cartwright C; Shaw K (Dove Medical Press, 2012)
Rachael Wade, Colleen Cartwright, Kelly ShawASLaRC Aged Services Unit, Health and Wellbeing Research Cluster, Southern Cross University, Coffs Harbour, NSW, AustraliaAim: This paper investigates the acceptance of in-home telehealth by frail older adults and carers of the Transition Care Program (TCP), and evaluates telehealth acceptance as a predictor for usage compliance.Method: A stratified random sample of participants was allocated to one of five groups: either a control group or to receive telehealth monitoring of their vital signs for a period of 12 or 24 weeks; with or without a medical alarm pendant.Results: Before being trained in and using telehealth, the majority of participants and carers demonstrated acceptance of the technology by reporting that they perceived it would be “useful” and “easy to use.” This acceptance was also reported post-TCP (up to 12 weeks of usage). The “perceived ease of use” of the telehealth equipment increased significantly from pre-telehealth training and usage to post-TCP (up to 12 weeks of usage) (P = 0.001). There was no change, (pre-training and usage to post-TCP) in the “perceived usefulness” of the telehealth equipment. The telehealth acceptance constructs of “ease of use” and “usefulness,” at pre-telehealth training and usage, approached statistical significance as a predictor of future compliance (P = 0.06). “Perceived ease of use,” at pre-training and usage, had a positive relationship with future compliance (P = 0.02).Conclusion: There is currently limited knowledge about the influences and determinants of home telehealth compliance in frail older people and their carers, potentially a significant user group for the technology into the future. This study’s finding that frail older people and their carers perceive that home telehealth is useful and easy to use demonstrates their acceptance of home telehealth as a therapeutic tool. Further, perceived ease of use of home telehealth is a significant predictor of compliance with frail older people and their carers’ use of home telehealth. Additional research is required in order to identify other influences and determinants of home telehealth compliance with this group. Knowledge about the influences and determinants of home telehealth compliance may assist the development of targeted interventions aimed at encouraging high compliance with users who are recording lower reading rates.Keywords: safety, older people, technology acceptance model, quasi-randomized controlled trial